EFL LEARNERS' ABILITY IN IDENTIFYING INDEPENDENT AND DEPENDENT CLAUSES: A DESCRIPTIVE STUDY AT UMMY SOLOK - Dimas Bambang Sadewo; Yuli Herman; Riyen Permata (Universitas Mahaputra Muhammad Yamin, 2026)
Clauses are one of the basic elements in English grammar. Identifying independent and dependent clauses helps students write correct and complete sentences. However, many EFL students still struggle to distinguish these clause types, especially dependent clauses. Previous studies mostly examined clause identification in general, without focusing on each dependent clause type separately. This study aimed to describe fourth-semester students' ability in identifying independent and dependent clauses at the English Education Department of FKIP UMMY Solok in the 2024/2025 academic year.This study used a descriptive quantitative design with 15 students selected through total sampling. Data were collected using a 20-item grammar test covering independent clauses, noun clauses, adjective clauses, and adverb clauses, then analyzed using percentage and mean score formulas. The results showed that students scored highest on independent clauses (mean: 7.06), followed by noun clauses (5.53), adverb clauses (4.80), and adjective clauses (4.46). Students had more difficulty with dependent clauses, particularly adjective and adverb clauses. Lecturers are encouraged to give more focused practice on dependent clauses to improve students' grammatical ability.